2019
DOI: 10.1111/acfi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Board interlocks and capital structure dynamics: evidence from China

Abstract: Using a sample of Chinese A-share listed companies from the Shanghai and Shenzhen stock exchanges from 2007 to 2016, this paper investigates the effects of director network centrality on the speed of capital structure adjustment. The results indicate that firms in the central position of the director network have a higher speed of capital structure adjustment and a lower extent of deviation from the target capital structure. This effect is mainly significant for non-stateowned enterprises (non-SOEs). Collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The results obtained are diverse, but in general positive as regards the relation between financial performance and participation in a business network (Cárdenas, 2014). These studies are mostly based on the resource dependence theory, demonstrating that personal links between a director and other members of company boards represent a preferential channel to access resources, information and legitimacy, with positive effects on firm profitability (Hillman et al ., 2009; Li et al ., 2019). Behind this theory is the assumption that the directors who participate in the interlocks are chosen to maximise the value of the firms, in favour of the interests of the stakeholders (Caiazza et al ., 2023).…”
Section: Theory Development and Study Hypothesesmentioning
confidence: 99%
“…The results obtained are diverse, but in general positive as regards the relation between financial performance and participation in a business network (Cárdenas, 2014). These studies are mostly based on the resource dependence theory, demonstrating that personal links between a director and other members of company boards represent a preferential channel to access resources, information and legitimacy, with positive effects on firm profitability (Hillman et al ., 2009; Li et al ., 2019). Behind this theory is the assumption that the directors who participate in the interlocks are chosen to maximise the value of the firms, in favour of the interests of the stakeholders (Caiazza et al ., 2023).…”
Section: Theory Development and Study Hypothesesmentioning
confidence: 99%
“…Well-connected independent directors accessed additional information and resources by serving on multiple company boards, which not only helped to reduce the likelihood of misstatements in financial reporting ( Omer et al, 2020 ) but also helped to improve management’s earnings forecasting accuracy ( Schabus, 2022 ). In addition, Li et al (2019) , Field et al (2013) and Feng et al (2019) have shown that independent directors located at the central location of the director networks played an important role in enhancing the efficiency of financing and improving IPO valuation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The lag is used, as it takes time for a firm Market ranking and network structure to reap the benefits from an interlock tie (Larcker et al, 2013), where beneficial knowledge exchange is unlikely to be instantaneous. Additionally, the use of lagged variables also aids in alleviating potential endogeneity effects (Li et al, 2019). Therefore, in this case the TNAM is defined as follows:…”
Section: Tnam Formulationmentioning
confidence: 99%